The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1182/blood-2007-02-072389
|View full text |Cite
|
Sign up to set email alerts
|

High-dose immunosuppressive therapy and autologous hematopoietic cell transplantation for severe systemic sclerosis: long-term follow-up of the US multicenter pilot study

Abstract: More effective therapeutic strategies are required for patients with poor-prognosis systemic sclerosis (SSc). A phase 2 single-arm study of high-dose immunosuppressive therapy (HDIT) and autologous CD34-selected hematopoietic cell transplantation (HCT) was conducted in 34 patients with diffuse cutaneous SSc. HDIT included total body irradiation (800 cGy) with lung shielding, cyclophosphamide (120 mg/kg), and equine antithymocyte globulin (90 mg/kg). Neutrophil and platelet counts were recovered by 9 (range, 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
180
1
18

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(210 citation statements)
references
References 38 publications
10
180
1
18
Order By: Relevance
“…Improved skin score and quality of life and at least stabilization of lung function were consistently reported in early phase II trials. [4][5][6][7][8] Recently, the phase II ASSIST 9 and the larger phase III ASTIS 10 prospective randomized trials showed better survival rates and improved skin, lung and functional status in patients treated with AHSCT as compared with monthly IV cyclophosphamide. Still, the transplant-related mortality reaching 10% and disease-progression rates of around 20-30% after AHSCT indicate that further improvements are still warranted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved skin score and quality of life and at least stabilization of lung function were consistently reported in early phase II trials. [4][5][6][7][8] Recently, the phase II ASSIST 9 and the larger phase III ASTIS 10 prospective randomized trials showed better survival rates and improved skin, lung and functional status in patients treated with AHSCT as compared with monthly IV cyclophosphamide. Still, the transplant-related mortality reaching 10% and disease-progression rates of around 20-30% after AHSCT indicate that further improvements are still warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Still, the transplant-related mortality reaching 10% and disease-progression rates of around 20-30% after AHSCT indicate that further improvements are still warranted. [6][7][8][9][10][11][12] Among current strategies to increase safety and efficacy of AHSCT, the benefit of ex vivo CD34+ positive selection of the graft remains debated. This study was therefore designed to evaluate the influence of ex vivo CD34+ selection on the outcome of SSc patients treated with AHSCT.…”
Section: Introductionmentioning
confidence: 99%
“…An approach that began in patients about 14 years ago, hematopoietic stem cell transplantation (HSCT), has been demonstrated to improve both skin and lung function as well as quality of life in patients with SSc 6,7,8 . Transplantation has been performed safely in some studies 8 , but results have been complicated by high treatment-related mortality in others 9 . Mortality of HSCT for SSc can be markedly reduced, however, if the reasons for mortality are properly recognized.…”
mentioning
confidence: 99%
“…Dark solid lines denote the mean and dashed lines represent the generalized estimating equation (GEE). Gray lines represent individual patient values (38). …”
Section: Figurementioning
confidence: 99%